Comparative transcriptomics indicates endogenous differences in detoxification capacity after formic acid treatment between honey bees and varroa mites - Antonia Genath (Nature Portfolio, 2020)
Abstract Formic acid (FA) has been used for decades to control Varroa destructor, one of the most important parasites of the western honey bee, Apis mellifera. The rather unselective molecular mode of action of FA and its possible effects on honeybees have long been a concern of beekeepers, as it has undesirable side effects that affect the health of bee colonies. This study focuses on short-term transcriptomic changes as analysed by RNAseq in both larval and adult honey bees and in mites after FA treatment under applied conditions. Our study aims to identify those genes in honey bees and varroa mites differentially expressed upon a typical FA hive exposure scenario. Five detoxification-related genes were identified with significantly enhanced and one gene with significantly decreased expression under FA exposure. Regulated genes in our test setting included members of various cytochrome P450 subfamilies, a flavin-dependent monooxygenase and a cytosolic 10-formyltetrahydrofolate dehydrogenase (FDH), known to be involved in formate metabolism in mammals. We were able to detect differences in the regulation of detoxification-associated genes between mites and honey bees as well as between the two different developmental stages of the honey bee. Additionally, we detected repressed regulation of Varroa genes involved in cellular respiration, suggesting mitochondrial dysfunction and supporting the current view on the mode of action of FA—inhibition of oxidative phosphorylation. This study shows distinct cellular effects induced by FA on the global transcriptome of both host and parasite in comparison. Our expression data might help to identify possible differences in the affected metabolic pathways and thus make a first contribution to elucidate the mode of detoxification of FA.